A platform for efficient genotyping in Musa using microsatellite markers - Christelova, P.; Valarik, M.; Hribova, E.; Houwe, Ines van den; Channelière, S.; Roux, N.; Doležel, Jaroslav (Oxford University Press, 2011)
The article reports on the first complex and standardized platform for molecular characterization of Musa germplasm that is ready to use for the wider Musa research and breeding community. The authors believe that this genotyping system offers a versatile tool that can accommodate all possible requirements for characterizing Musa diversity, and is economical for samples ranging from one to many accessions.